Volume Transmission and Pain Perception - Gilberto C. Castañeda-Hernàndez; Paul Bach-y-Rita (The Scientific World Journal)
Volume transmission (VT) is the diffusion through the brain extracellular fluid of neurotransmitters released at points that may be remote from the target cells with the resulting activation of extrasynaptic receptors. VT appears to play multiple roles in the brain in normal and abnormal activity, brain plasticity and drug actions. The relevance of VT to pain perception has been explored in this review.